Accessibility of youth-friendly sexual and reproductive health services to secondary school adolescents in Southern Cross River, Nigeria - Eneji, Rosemary I.; Odey, Stephen Adi; Adinya, Odey John; Etobe, Eteng Ikpi; Odinka, Godfrey Ekene (Edelweiss Applied Science and Technology, 2025)
Sexual and reproductive health behaviors are the main causes of death, disability, and disease among adolescents in Nigeria. In this study, we determined the accessibility of youth-friendly sexual and reproductive health services to secondary school adolescents in southern Cross River State, Nigeria. Nineteen randomly selected public secondary schools across the seven local government areas in the zone were used. The respondents were four hundred senior secondary (SSI - SS3) students, aged 15-19 years, comprising 63.7% females and 36.3% males. A 50-item structured questionnaire was used for the study. There was a strong influence of age and sex of adolescents, income and occupation of parents, knowledge and awareness of adolescents, and tradition on the accessibility and use of youth-friendly sexual and reproductive health services (YFSRHS) by the adolescents. The attitude of health workers regarding accessibility had little effect. Overall, youth-friendly sexual and reproductive health services were not easily accessible to adolescents in the study area. Thus, there is a need to enforce adolescent reproductive health policies in the area. Training and the use of trained caregivers and peer educators to attend to adolescents, as well as the inclusion of adolescent reproductive health as a subject in the curriculum, are strongly recommended.